2021
DOI: 10.37039/1982.8551.20210025
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoretinitis pigmentosa due to syphilis: a case report and literature review

Abstract: Syphilis is a sexually transmitted infection caused by the spirochete Treponema pallidum. Ocular involvement can occur at any time, and it may affect 10% of patients in the secondary stage, and from 2% to 5% in the tertiary stage. Uveitis is the most common presentation of ocular syphilis, affecting 0.4% to 8% of patients with systemic disease. Chorioretinitis is the most common posterior alteration. We present the case of a 53-year-old male patient, presenting with bilateral low visual acuity and nyctalopia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Examination revealed anterior vitreous cells, arteriolar attenuation, diffuse RPE atrophy, and retinal pigmentary changes bilaterally, with extinguished ffERG readings in both eyes. Initially presumed to have RP, this patient was later diagnosed with syphilis, as confirmed by a positive FTA-Abs immunoglobulin G test [24]. In contrast to patients with RP, patients with ocular syphilis may present with a unilateral or asymmetric bilateral patchy chorioretinitis that can rapidly progress, culminating in chorioretinal scars in late stages [25].…”
Section: Chorioretinal Infectionsmentioning
confidence: 85%
“…Examination revealed anterior vitreous cells, arteriolar attenuation, diffuse RPE atrophy, and retinal pigmentary changes bilaterally, with extinguished ffERG readings in both eyes. Initially presumed to have RP, this patient was later diagnosed with syphilis, as confirmed by a positive FTA-Abs immunoglobulin G test [24]. In contrast to patients with RP, patients with ocular syphilis may present with a unilateral or asymmetric bilateral patchy chorioretinitis that can rapidly progress, culminating in chorioretinal scars in late stages [25].…”
Section: Chorioretinal Infectionsmentioning
confidence: 85%
“…It is often found to be "consistent with retinal pigment epithelium degeneration", present along the retinal veins and choroidal vessels [2,9,18,[33][34][47][48][49]. Some studies also reported "hyper uorescence rings", with one case series of four patients reporting demarcation lines too [47,[51][52][53][54]. A window defect is an area of hyper uorescence, arising when the retinal pigment epithelium (RPE) is damaged and there is an absence of pigmentation.…”
Section: Symptomsmentioning
confidence: 99%
“…The full-eld electroretinogram (ffERG) is an electrophysiologic test, assessing retinal functioning through exposure to a full-eld light-stimulus. Eleven studies reported decreased scotopic and photopic waves [3,11,18,20,23,25,32,46,52,60], whilst 7 studies reported decreased a-and b-wave amplitudes [3,11,18,20,23,46,52]. Damaged or dysfunctional photoreceptors of rods and cones were found in a few PPRCA patients [16,34,58].…”
Section: Symptomsmentioning
confidence: 99%